(untitled) (Gestión y Gerencia, 2020)
A year of beginnings, of stumbling blocks in the political, economic, academic, commercial and health fields, at least for our country. However, on a global level, the health convulsion caused by the Covid-19 pandemic shook the human race. Certainly, since March 2020, activities have been suspended and the education sector has obviously not escaped this reality, so most of the learning and training centers from Elementary schools to universities closed their doors. In a slow way that happened and everything was adjusting and the academic tasks and responsibilities were closing. Everything began to work more or less from home of teachers, secretaries, administrative and technical employees and eventually meetings with the recommended protections and distances. A year of transformation as we have seen in all areas and our review also entered into this process. Transformation that was already being felt with the direction change sharpened at the end of 2019 which paralyzed us for almost a year. After thirteen years of continuous work, we decided to reorganize and consider publishing the journal every six months. It has not been easy to adapt, it has required effort, patience, constancy and time for adjustments, in a practically closed academic environment, subject to interruption of connections and with the fear of contagion, which limited necessary tasks of group activity even with the material of authors who had considered the journal as a window of communication, depositing research results, essays and practices of support to companies.